The Analysis of Constructing Sentences in Semester III STBA JIA in Academic Year 2022/2023 - Surista, Ade; Setiawan, Wawan (Sekolah Tinggi Bahasa Asing JIA, 2023)
This research aimed to describe how the student’s constructing sentences in their writing descriptive paragraph. The sample uses are the students of semester III class A, B and evening class with the total number of students are 41 students. The instrument uses in this research are test and interview. The researcher limits the sentences constructing are simple, compound and complex sentences. It assumed that the students are able to construct and use simple sentences, compound sentences and complex sentence in developing descriptive writing. The result show that from the first test, the average is 79. In the second test, from 41 students, there are 12 students do all correct sentences. There are 9 students made mistakes in simple sentence, with 10 mistakes. For compound sentence, there are 18 students who made 35 mistakes. and complex sentences, there are 18 students who made 41 mistakes.